Opposing role of tumor necrosis factor receptor 1 signaling in T cell–mediated hepatitis and bacterial infection in mice. Issue 2 (18th April 2016) - Wroblewski, Raluca; Armaka, Marietta; Kondylis, Vangelis; Pasparakis, Manolis; Walczak, Henning; Mittrücker, Hans‐Willi; Schramm, Christoph; Lohse, Ansgar W.; Kollias, George; Ehlken, Hanno
Abstract : Death receptor (DR) ligands such as tumor necrosis factor (TNF) have been identified as fundamental mediators of liver damage both in mouse models and in humans. While the essential site of function of DR signaling is conceivably the hepatocyte, a systematic analysis is missing. Using mice with conditional gene ablation, we analyzed the tissue‐specific function of DR signaling in T cell–dependent (concanavalin A) and independent (lipopolysaccharide/galactosamine) hepatitis and in models of bacterial infection ( Listeria monocytogenes, lipopolysaccharide). We report that lipopolysaccharide/galactosamine‐induced liver injury depends on hepatocyte‐intrinsic TNF receptor 1 (p55, TNFR1). In contrast, we show that T cell–induced hepatitis was independent of TNFR1 signaling in hepatocytes, T cells, or endothelial cells. Moreover, T cell–induced hepatitis was independent of hepatocyte‐intrinsic Fas‐associated protein with death domain, TNF‐related apoptosis‐inducing ligand receptor, or Fas signaling. Instead, concanavalin A–induced hepatitis was completely prevented in mice with myeloid‐derived cell (MDC)–specific deletion of TNFR1. Significantly, however, mice lacking TNFR1 in MDCs succumbed to listeria infection, although they displayed similar sensitivity toward endotoxin‐induced septic shock when compared to control mice. These results suggest that TNFR1 signaling in MDCs is a critical mediator of both the detrimental and the protective functions of TNF in T cell–induced hepatitis and bacterial infection, respectively. Conclusion : The critical site of action of DRs is completely dependent on the nature of hepatitis; the data specify MDCs as the essential cell type of TNFR1 function in T cell–mediated hepatitis and in the response to listeria, thereby identifying the opposing role of MDC TNFR1 in autoimmunity and bacterial infection. (Hepatology 2016;64:508‐521)